Ferroptosis in the adjuvant treatment of lung cancer-the potential of selected botanical drugs and isolated metabolites - Tian, Xiaoyan; Fu, Kunling; Huang, Xuemin; Zou, Haiyan; Shi, Nianmei; Li, Jiayang; Bao, Yuxiang; He, Sisi; Lv, Junyuan (Frontiers in Pharmacology, 2024)
Ferroptosis represents a distinct form of cell death that is not associated with necrosis, autophagy, apoptosis, or pyroptosis. It is characterised by intracellular iron-dependent lipid peroxidation. The current literature indicates that a number of botanical drugs and isolated metabolites can modulate ferroptosis, thereby exerting inhibitory effects on lung cancer cells or animal models. The aim of this review is to elucidate the mechanisms through which botanical drugs and isolated metabolites regulate ferroptosis in the context of lung cancer, thereby providing potential insights into lung cancer treatment. It is crucial to highlight that these preclinical findings should not be interpreted as evidence that these treatments can be immediately translated into clinical applications. In the future, we will continue to study the pharmacology, pharmacokinetics and toxicology of these drugs, as well as evaluating their efficacy and safety in clinical trials, with the aim of providing new approaches to the development of new agents for the treatment of lung cancer.